Design of Newly Developed Burner Rig Operating with Hydrogen Rich Fuel Dedicated for Materials Testing - Nowak, Wojciech J.; Drajewicz, Marcin; Góral, Marek; Smusz, Robert; Cichosz, Piotr; Majka, Andrzej; Sęp, Jarosław (Advances in Mechanical and Materials Engineering, 2023)
The main purpose of present article is to present the burner rig station newly developed at the Rzeszow University of Technology in Poland. The burner rig is dedicated to operate on fuels rich in hydrogen. The burner rig is able to operate with fuels with hydrogen content up to 50 volume %. A detailed description of burner rig construction is presented. Moreover a mathematical model predicting temperature distribution within the combustion chamber is presented. The obtained results showed a good insulation of burner rig construction leading to the temperature gradient from 1674℃ in the burner rig to 214℃ on steel housing.